2016
DOI: 10.5530/jppcm.2016.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of mass gathering (Hajj) pharmaceutical care program in Saudi Arabia

Abstract: Introduction: Once a year, Muslims of every ethnic group, the Hajj is the fifth and final pillar of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…After one year several newly established projects started and others update and improve them. The newly formed nine projects of IVDS look like what found with Alomi and his colleague's studies 19,[21][22] and reach the same services what found by Alsaltan et al 2 In the pharmacy total quality management, there were one projects newly established at all hospital pharmacies while three projects applied at one hospital only because it was requested by hospital total quality management while another hospital did not seek it. The new projects like patient satisfaction program, as found in Alomi et al studies.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…After one year several newly established projects started and others update and improve them. The newly formed nine projects of IVDS look like what found with Alomi and his colleague's studies 19,[21][22] and reach the same services what found by Alsaltan et al 2 In the pharmacy total quality management, there were one projects newly established at all hospital pharmacies while three projects applied at one hospital only because it was requested by hospital total quality management while another hospital did not seek it. The new projects like patient satisfaction program, as found in Alomi et al studies.…”
Section: Discussionsupporting
confidence: 66%
“…[19][20] A representative from GAPC with extensive period experience of pharmacy practice, pharmacy administration, and clinical pharmacy visited three great and major hospitals in Riyadh city. The expert clinical pharmacist visited the pharmacy services 1-2 day per week per each hospital, discussed with the director of the pharmacy all projects need to newly established or improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The study made as an electronic format, and it analyzed through survey monkey system and Microsoft Excel version ten. The authors suggested some solution to improve the scoring medication safety culture and the finding of ISMP self-assessment, the 5-points Likert scale system with high priority or opportunity to implement (5) and low priority or opportunity to implement (1). Those suggestions based on General Administration of Pharmaceutical strategic goals and Saudi Central Board for Accreditation of Health Care Institutions (CBAHI) standards in Saudi Arabia.…”
Section: Methodsmentioning
confidence: 99%
“…In this period, several policy and procedures of drug preparation launched. [1] The administration distributed six booklets of parenteral dilution manual for adults and pediatric and neonates. In addition to, the parenteral dilution manual for home health care services.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, some hospitals during mass girthing started comprehensive patient medication education with more five languages. [5] The Institution of Safe Medication Practice (ISMP) formulated self-assessment tool for medication safety at hospitals, patient education, and pharmacy quality were key elements among them. [6] Those tools handy to measure the medication safety culture related both elements.…”
Section: Introductionmentioning
confidence: 99%